Taste alteration in COVID-19: Significant geographical differences exist in the prevalence of the symptom - Nicola Cirillo (Elsevier, 2021)
Early detection of COVID-19 is important for reduction in the spread of the disease and gustatory disturbances (GD) are known to have a strong predictive value. In the present study, we aimed to map the geographical differences in the prevalence of GD in individuals infected with SARS-CoV-2 during the first wave of COVID-19 in order to improve case identification and to facilitate prioritization. We undertook a rapid scoping review of articles published in the repository of the National Library of Medicine (MEDLINE/PubMed) and medRxiv from their inception until 3rd September, 2020. The minimum requirements for completing a restricted systematic review were fulfilled. Of the 431 articles retrieved, 61 studies (28,374 cases confirmed with COVID-19) from 20 countries were included in the analysis. GD were most prevalent in the Americas [66.78%, 95% CI 54.77-78.79%] compared to Europe [57.18%, 95% CI 52.35-62.01%], the Middle East [38.83%, 95% CI 27.47-50.19%] and East Asia [13.1%, 95% CI 0.14-26.06%]. No differences of GD prevalence were evident between February and August 2020. The data demonstrate that there is a marked geographical distribution of GD in COVID-19 patients which, possibly, might be explained by differences in diagnostic criteria for COVID-19 case definition during the early phase of the pandemic.